Handgrip Strength and Blood Pressure in Children and Adolescents: Evidence From NHANES 2011 to 2014. (26th February 2018) - Zhang, Rui; Li, Changwei; Liu, Tingting; Zheng, Liqiang; Li, Shengxu
Abstract: BACKGROUND: Previous studies have reported that handgrip strength, a measure of muscular fitness, is associated with cardiovascular risk factors. However, the association of handgrip strength with blood pressure (BP) in children has been inconsistent. We tested the association of handgrip strength with systolic and diastolic BP in children and adolescents from the National Health and Nutrition Examination Survey (NHANES) 2011–2014. METHODS: The study included 3, 929 participants aged 8–19 years who underwent a handgrip test. The sum of the maximum handgrip strength from both hands was used. General linear models were used to examine the associations between handgrip strength and the outcome variables. RESULTS: After adjustment for age, race, sex, body mass index, and physical activities, handgrip strength was significantly and positively associated with systolic ( P < 0.0001) and diastolic ( P = 0.01) BP. There was an increasing trend in systolic BP as handgrip strength increased from the bottom quartile to the top quartile, with 2.1 mm Hg difference between the top and the bottom quartiles ( P for trend <0.0001). Similar results were observed for diastolic BP. CONCLUSIONS: Muscular fitness is positively associated with BP in children and adolescents. The implications and underlying mechanisms for these results need further examinations.